Instant Swamp - Miki, Satoshi; Kimura, Shinya; Aso, Kumiko; Kazama, Morio; Kase, Ryo (Third Window Films, 2010)
Haname is a lively young journalist blessed with an exceedingly vivid imaginative working for a woman's magazine on the brink of bankruptcy. Her daily diet of gloopy health drinks aren't enough to shield her from what she perceives as a particularly severe run of bad luck, which all began on her eighth birthday when her father stormed out of the house, not only abandoning her, but flinging all her toys into a nearby swamp, including a cat talisman which she thinks must have been cursed. Haname sets out to retrieve her lost possessions, a quest which reacquaints her with her father, now a hippie working at a junk shop who goes under the name "Light Bulb" , and brings her into contact with a punk named Gus. [Cover]
Keywords: DVD-Video